Prevalence of reported food allergies in Brazilian preschoolers living in a small Brazilian city - José A. da S. Correia; Adriana Azoubel Antunes; Luiz Taborda-Barata; José Laerte Boechat; Emanuel Sávio Cavalcanti Sarinho (Allergy, Asthma & Clinical Immunology, 2022)
Abstract Introduction Although the prevalence of allergic diseases, including food allergies, has increased over recent decades, relevant information on this topic is still lacking, particularly in younger children living in small cities. Objective To investigate the prevalence of reported food allergies in preschoolers in Limoeiro/Pernambuco, Brazil. Methods This was a cross-sectional study with preschoolers. Parents/guardians of all preschoolers enrolled at municipal schools between March and June 2019 (total of 619) were invited to complete a screening questionnaire (total of 619). Another 151 questionnaires were applied on the streets of the town. For positive responses, a second, more detailed and validated questionnaire was completed. Results A total of 412 questionnaires were returned, of which, 47 presented a positive response to food allergies and only 29 (7.04%) identified a particular food. The most frequently reported food items were shrimp, mollusks, pork, fruit and milk. Of the 29 who identified foods, 22 responded to the detailed questionnaire, resulting in only 4 (0.97%) positive responses. Of these, two were later discarded through clinical examinations and an open oral provocation test, resulting in a final prevalence of 0.48% of confirmed food allergies. Conclusion The prevalence of reported food allergies was lower than that described in previous studies. The most commonly mentioned foods were shrimp, mollusks and pork, with more reports of multiple food allergies, even in children who had never been previously exposed to these possible allergens, which highlights the relevance of perception in reported food allergy studies.